Opportunities for nano-formulations in type 2 diabetes mellitus treatments - Jeevanandam, J.; Danquah, Michael; Debnath, Sujan; Meka, V.; Chan, Yen S. (2015)
Diabetes mellitus has been a threat to humans for many years. Amongst the different diabetes types, type 2 diabetes mellitus is the most common, and this is due to drastic changes in human lifestyle such as lack of exercise, stressful life and so on. There are a large number of conventional treatment methods available for type 2 diabetes mellitus. However, most of these methods are curative and are only applicable when the patient is highly symptomatic. Effective treatment strategies should be geared towards interfering with cellular and bio molecular mechanisms associated with the development and sustenance of the disease. In recent years, research into the medical potential of nanoparticles has been a major endeavor within the pharmaceutical industries. Nanoparticles display unique and tuneable biophysical characteristics which are determined by their shape and size. Nanoparticles have been used to manifest the properties of drugs, and as carriers for drug and vaccine delivery. Notwithstanding, there are further opportunities for nanoparticles to augment the treatment of a wide range of life threatening diseases that are yet to be explored. This review article seeks to highlight the application of potential nano-formulations in the treatment of type 2 diabetes mellitus. In addition, the activity of nanomedicine supplements in reversing insulin resistance is also discussed.